Synergistic effects on char and oil produced by the co-pyrolysis of pine wood, polyethylene and polyvinyl chloride. (15th October 2018) - Lu, Peng; Huang, Qunxing; (Thanos) Bourtsalas, A.C.; Chi, Yong; Yan, Jianhua
Highlights: Plastic-biomass interaction promoted biomass decomposition. More oil and less char were produced from co-pyrolysis of pine wood and PE. Less oil and more char were produced from co-pyrolysis of pine wood and PVC. Plastic-biomass interaction improved quality of oil and chemical stability of char. Abstract: The synergistic effects of the woody biomass (pine wood (PW)) and plastics (polyethylene (PE) and polyvinyl chloride (PVC)) during co-pyrolysis on the properties of char and oil were examined by thermogravimetric analysis (TGA) and fixed bed reactor. The results showed that PW-PE interaction increased the maximum weight loss rate of PW by 8.0–23.7%. Co-pyrolysis of PW-PE blends produced lower quantity of char (13.8–22.4%) and higher quantity of oil (3.7–4.4%) as compared to the theoretical results. PW-PVC interaction decreased the temperature corresponding to the maximum weight loss rate of PW by 47–51 °C. Co-pyrolysis of PW-PVC blends yielded more char (15.5–27.9%) and less oil (7.2–14.4%) than expected values. Also, the interaction of biomass and plastic materials decreased the H/C atomic ratio of char, which resulted in a higher chemical stability of char. The fuel quality of oil produced from mixtures was improved due to a lower O/C atomic ratio of oil as compared to the theoretical results.